HODGKIN LYMPHOMA: AN UPDATE ON ITS BIOLOGY WITH NEWER INSIGHTS INTO CLASSIFICATION - Mani, Haresh (2009)
In the last few years, there has been a greater understanding of the spectrum and biology of Hodgkin lymphoma. In standard texts, Hodgkin lymphoma is classified as two distinct entities, namely nodular lymphocyte predominant Hodgkin lymphoma and classical Hodgkin lymphoma. However, recent evidence suggests that classical Hodgkin lymphoma is not a single disease. While the mixed cellularity and lymphocyte depleted subtypes may be part of a biologic continuum, the nodular sclerosis subtype has a distinct epidemiology, clinical presentation and histology. Nodular sclerosis Hodgkin lymphoma may also be related to primary mediastinal B-cell lymphoma and mediastinal grey zone lymphomas. We present an update on the pathobiology of Hodgkin lymphoma and discuss these biologic and clinical differences in this review.